HMGB1-dependent signaling in the regulation of mast cell activity during inflammation - Agier, Justyna; Różalska, Sylwia; Wiktorska, Magdalena; Kozłowska, Elżbieta; Jurczak, Magdalena; Nowak, Monika; Żelechowska, Paulina (Frontiers in Immunology, 2025)
BackgroundDamaged cells release endogenous molecules known as alarmins into the extracellular space following cellular injury. Alarmins may function as adjuvants by interacting with PRRs to indicate danger and initiate a localized sterile inflammatory response, which facilitates tissue regeneration. A pivotal alarmin is HMGB1, which is internalized through the RAGE to notify adjacent cells about compromised homeostasis. Given the significant role of mast cells (MCs) in inflammatory processes and the critical nature of alarmins as indicators of danger, this study evaluates the hypothesis that MCs serve as essential sensors of cellular injury. The present study investigates whether HMGB1 affects the expression levels of specific PRRs in mature MCs. These receptors include Dectin-1 and Dectin-2, TLR2, NOD1, and RIG-I. Furthermore, this study aims to determine whether HMGB1 modulates the inflammatory response of these cells, which encompasses the production of cytokines, chemokines, ROS, histamine, and cysLTs, as well as their migration patterns. Moreover, the research aims to investigate the role of RAGE and the involvement of signaling molecules in the activation of MCs mediated by HMGB1.MethodsAll experiments were carried out using in vivo differentiated, mature tissue MCs freshly isolated from the rat peritoneal cavity. The potency of HMGB1 to provoke MC PRR expression, generation, and/or release of a panel of mediators and migration was investigated.ResultsHMGB1 markedly enhances the expression of Dectin-1, RIG-I, and NOD1, while simultaneously stimulating MCs to produce CCL3, IL-1β, TNF, cysLTs, histamine, and ROS. This protein acts as a potent chemoattractant for MCs. The administration of RAGE antagonist to MCs significantly attenuated the generation of mediators and the migratory response, thereby confirming the receptor’s involvement in the response of HMGB1-treated cells. Intracellular signaling in MCs activated by HMGB1 involves ERK1/2, p38 MAPK, PI3K, NF-κB, and, in part, JAK2.ConclusionsThe data robustly support the notion that HMGB1 is an important endogenous alarmin that promotes and enhances MC activity in inflammatory processes. These insights highlight HMGB1 as a potential therapeutic target for regulating MC-driven inflammatory disorders, which encompass allergy, autoimmune diseases, and chronic conditions.